Tribo-electro-catalytic dye degradation driven by mechanical friction using MOF-derived NiCo2O4 double-shelled nanocages. (15th April 2022) - Ruan, Lujie; Jia, Yanmin; Guan, Jingfei; Xue, Bei; Huang, Shihua; Wang, Zhenhua; Fu, Yanghe; Wu, Zheng
Abstract: As a common energy in everyday life, friction can be harvested and converted into electricity energy via triboelectricity to electrochemically drive the degradation of the organic dye in wastewater, which can be named as tribo-electro-catalysis. In this work, tribo-electro-catalytic performance have been systematically characterized in the MOF-derived NiCo2 O4 double-shelled nanocage catalyst, which was synthesized via a liquid phase method using zeolite imidazole frameworks (ZIF)-67 as template with the subsequent calcination. The SEM/TEM, XRD/XPS, and BET have been respectively employed to analyze the microscopy, the crystal structure and the specific area of the synthesized catalysts. The tribo-electro-catalytic performance was evaluated through the dye degradation ability of the MOF-derived NiCo2 O4 double-shelled nanocage under the friction force between mechanical stirring magneton and the catalyst's surface. It has found that the tribo-electro-catalytic Rhodamine B (RhB) dye degradation ratio can reach ∼98.6% after stirring the catalyst at room temperature for 56 h in dark. The tribo-electro-catalytic RhB degradation is inseparable from the coexistence of catalyst and contact between the stirring magneton and catalyst. The active species quenching experiments demonstrate that the main active species are the positive charges, the negative charges and the superoxide radicals. The tribo-electro-catalysis is originated from the triboelectricity driven by the friction between magneton and catalyst. Furthermore, it is also found that enlarging the contact area between catalyst and magneton through increasing the number or length of magnetons can effectively enhance the tribo-electro-catalytic performance. Finally, the durability of tribo-electro-catalysis has been revealed via the multiple recycling utilization experiments. This work clearly shows its application for the tribo-electro-catalytic dye degradation, which represents a promising application for harvesting the mechanical friction energy. Graphical abstract: Image 1 Highlights: Double-shelled nanocages NiCo2 O4 has been synthesized via the liquid phase method with the subsequent calcination. NiCo2 O4 exhibits the tribo-electro-catalysis and the recycling utilization durability for Rhodamine B dye degradation. The positive and negative charges and superoxide radical are the major active species in tribo-electro-catalysis. After 56 h friction in dark, the tribo-electro-catalytic Rhodamine B dye degradation ratio reaches ~98.6%.